Pengaruh Islamic Social Reporting dan Islamic Corporate Governance terhadap Kinerja Keuangan Perusahaan - Nida Siti Nabila; H.Azib (Bandung Conference Series: Business and Management, 2022)
Abstract. This study aims to determine whether there is an influence of Islamic Social Reporting which consists of the concepts of individual education, justice, and benefit and Islamic Corporate Governance on Financial Performance at Islamic Commercial Banks in Indonesia in 2015-2019 with secondary data analysis using quantitative methods. The analytical tool used is multiple linear regression with the help of IBM SPSS Statistics 22. The results of this study indicate that the variable Islamic Corporate Governance has an effect on Financial Performance. While the Islamic Social Reporting variable partially has no significant effect on Financial Performance. Simultaneously Islamic Corporate Governance and Islamic Social Reporting have a significant effect on Financial Performance with an R square value of 21.4%. This means that the independent variable is able to explain the dependent variable by 21.4%, and the rest is explained by other variables not examined in this study. Abstrak. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh Islamic Social Reporting yang terdiri dari konsep pendidikan individu, keadilan, dan kemaslahatan dan Islamic Corporate Governance tehadap Kinerja Keuangan pada Bank Umum Syariah di Indonesia tahun 2015-2019 dengan analisis data sekunder menggunakan metode kuantitatif. Alat analisis yang digunakan adalah regresi linier berganda dengan bantuan IBM SPSS Statistics 22. Hasil penelitian ini menunjukkan bahwa variabel Islamic Corporate Governance berpengaruh terhadap Kinerja Keuangan. Sedangkan variabel Islamic Social Reporting secara parsial tidak berpengaruh signifikan terhadap Kinerja Keuangan. Secara simultan Islamic Corporate Governance dan Islamic Social Reporting berpengaruh secara signifikan terhadap Kinerja Keuangan dengan nilai R square sebesar 21,4%,. Hal ini berarti bahwa variabel independen mampu menjelaskan variabel dependen sebesar 21,4%, dan sisanya dijelaskan oleh variabel lain yang tidak diteliti dalam penelitian ini.